High-Intensity Interval Training: A Potential Exercise Countermeasure During Human Spaceflight - Hurst, Christopher; Scott, Jonathan P. R.; Weston, Kathryn L.; Weston, Matthew (Frontiers in Physiology, 2019)
High-intensity interval training (HIT) is an effective approach for improving a range of physiological markers associated with physical fitness. A considerable body of work has demonstrated substantial improvements in cardiorespiratory fitness following short-term training programmes, while emerging evidence suggests that HIT could also have the ability to positively impact aspects of neuromuscular fitness. Given the detrimental consequences of prolonged exposure to microgravity on both of these physiological systems and the potential for HIT to impact multiple components of fitness simultaneously, HIT is an appealing exercise countermeasure during human spaceflight. As such, the primary aim of this mini-review is to synthesise current terrestrial knowledge relating to the effectiveness of HIT for inducing improvements in cardiorespiratory and neuromuscular fitness. As exercise-induced fitness changes are typically influenced by the specific exercise protocol employed, we will consider the effect of manipulating programming variables, including exercise volume and intensity, when prescribing HIT. In addition, as the maintenance of HIT-induced fitness gains and the choice of exercise mode are important considerations for effective training prescription, these issues are also discussed. We conclude by evaluating the potential integration of HIT into future human spaceflight operations as a strategy to counteract the effects of microgravity.